Design and implementation of a high-order buck-boost DC-DC converter - Lau, Jia Zhi (2016)
In this report, the design and implementation of a high-order buck-boost DC-DC converter system was presented. Various controllers for the regulation of the converter were implemented and having their performance evaluated. These includes current mode control, sliding mode with hysteresis control and adaptive current control. Experimental results were presented to illustrate the performance of the controllers under various operating conditions.